2019
DOI: 10.1126/sciadv.aax2476
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial morphogenetic and mechanical cues to mimic bone development for defect repair

Abstract: Endochondral ossification during long bone development and natural fracture healing initiates by mesenchymal cell condensation, directed by local morphogen signals and mechanical cues. Here, we aimed to mimic development for regeneration of large bone defects. We hypothesized that engineered human mesenchymal condensations presenting transforming growth factor–β1 (TGF-β1) and/or bone morphogenetic protein-2 (BMP-2) from encapsulated microparticles promotes endochondral defect regeneration contingent on in vivo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 68 publications
2
49
1
1
Order By: Relevance
“…A robust cartilage template exhibiting zonal architecture with both mature and hypertrophic chondrocytes that was actively remodeled into trabecular bone through endochondral ossification was observed, and the presence of cortical bone-like structures indicated engagement of intramembranous ossification with spatial fidelity. Upon implantation in femoral segmental defects, stabilized with custom internal compliant fixation plates that allow for the delayed commencement of in vivo mechanical loading after four weeks of stable fixation (34,(37)(38)(39), engineered hMSC tubes induced more robust bone healing compared to loosely-packed hMSC sheets with defect bridging achieved in the majority of critical-size defects. New bone was formed through endochondral ossification in both groups; however, only hMSC tubes induced regenerate tissue that partially resembled the normal growth plate architecture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A robust cartilage template exhibiting zonal architecture with both mature and hypertrophic chondrocytes that was actively remodeled into trabecular bone through endochondral ossification was observed, and the presence of cortical bone-like structures indicated engagement of intramembranous ossification with spatial fidelity. Upon implantation in femoral segmental defects, stabilized with custom internal compliant fixation plates that allow for the delayed commencement of in vivo mechanical loading after four weeks of stable fixation (34,(37)(38)(39), engineered hMSC tubes induced more robust bone healing compared to loosely-packed hMSC sheets with defect bridging achieved in the majority of critical-size defects. New bone was formed through endochondral ossification in both groups; however, only hMSC tubes induced regenerate tissue that partially resembled the normal growth plate architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to our study include (i) the difference in pre-culture time between hMSC tubes and sheets, and (ii) the small number of femoral defect samples. To the former, for consistency with previous in vivo studies (33,38,39), we elected to implant day 2 hMSC sheets in comparison to day 8 hMSC tubes. Condensations were matched in cell number, microparticle concentration, and morphogen dosing; however, the additional six days in culture facilitated greater chondrogenic priming of hMSC tubes vs. sheets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The repair of large bone defects caused by traumas, infections, cancers, or other diseases is still a thorny clinical problem (Herberg et al, 2019). Previous studies have shown that osteo-inductive growth factors played a significant role in bone regeneration (Cui L. et al, 2019;Ruehle et al, 2019) however, autologous bone graft remains the gold standard in the treatment of bone defects (Bouyer et al, 2016).…”
Section: Applications In Bone Tissue Engineeringmentioning
confidence: 99%